CRISPR/Cas12a-Based Diagnostic Platform Accurately Detects Nocardia farcinica Targeting a Novel Species-Specific Gene - Qiu, Xiaotong; Xu, Shuai; Liu, Xueping; Ren, Hongtao; Han, Lichao; Li, Zhenjun (Frontiers in Cellular and Infection Microbiology, 2022)
In this study, a novel nucleic acid detection platform, which combined CRISPR/Cas12a-based detection with loop-mediated isothermal amplification (LAMP), was developed and termed CRISPR-CLA. In the CRISPR-CLA system, LAMP preamplification was employed, and CRISPR/Cas12a-based detection was used to monitor the preamplicons. The forward inner primer (FIP) was engineered with a protospacer adjacent motif (PAM) site TTTA of Cas12a effector at the linker region; thus, the CRISPR-CLA platform can detect any sequence as long as the primer design meets the requirement of LAMP. To demonstrate the validity of the CRISPR-CLA system, it was applied for the molecular diagnosis of nocardiosis caused by Nocardia farcinica (N. farcinica). A highly conserved and species-specific gene pbr1 of N. farcinica, which was first reported in this study, was used as the target of detection. A set of LAMP primers targeting a fragment of pbr1 of the N. farcinica reference strain IFM 10152 was designed according to the principle of CRISPR-CLA. Three CRISPR RNAs (crRNAs) with different lengths were designed, and the most efficient crRNA was screened out. Additionally, three single-strand DNA (ssDNA) probes were tested to further optimize the detection system. As a result, the N. farcinica CRISPR-CLA assay was established, and the whole detection process, including DNA extraction (20 min), LAMP preamplification (70 °C, 40 min), and CRISPR/Cas12a-mediated detection (37 °C, 8 min), can be completed within 70 min. A fluorescence reader (for fluorescence CRISPR-CLA) or a lateral flow biosensor (for lateral-flow CRISPR-CLA) can be the media of the result readout. Up to 132 strains were used to examine the specificity of N. farcinica CRISPR-CLA assay, and no cross-reaction was observed with non-N. farcinica templates. The limit of detection (LoD) of the N. farcinica CRISPR-CLA assay was 100 fg double-strand DNA per reaction. N. farcinica was recognized accurately in 41 sputum specimens using the N. farcinica CRISPR-CLA assay, which was better than a previous PCR method. Hence, the N. farcinica CRISPR-CLA assay is a rapid, economic and accurate method to diagnose N. farcinica infection.